Religious beliefs and practices toward HPV vaccine acceptance in Islamic countries: A scoping review. - Sezer Kisa; Adnan Kisa (PLoS ONE)
Background Despite the availability of effective HPV vaccines, their acceptance in Islamic countries is often influenced by religious beliefs, practices, and misconceptions. Objective This review aimed to identify the current literature on the religious beliefs and any misconceptions toward HPV vaccine acceptance within the Organisation of Islamic Cooperation (OIC) countries. Method Using key terms, a systematic search in MEDLINE/PubMed, Embase, and CINAHL yielded 23 studies that met the inclusion and exclusion criteria. The scope of this review included all research articles published in English until October 31, 2023. A form based on the aim of the study was developed and used to extract the data. Results The review highlights the complexity of the relationship between religious beliefs and HPV vaccine uptake. The findings reveal significant objections among a number of Muslims. Some of them believe vaccines lead to infertility and sexual promiscuity, defy religious norms, are a sneaky way to inject good Muslims with haram ingredients, and are an abandonment of righteous principles in general. Conclusions Vaccine hesitancy is a result of doubts regarding the vaccine's safety, necessity, and compatibility with religious beliefs. It is recommended to encourage HPV vaccine uptake in Islamic countries by using public health strategies that adopt a holistic approach that incorporates religious, cultural, and social aspects.